solve:-
( 2y + 3 ) / ( 3y + 2 ) = ( 4y + 5 ) / ( 6y + 7)
Answers
Answered by
1
Step-by-step explanation:
ans in the pic hope it helps u
Attachments:
![](https://hi-static.z-dn.net/files/df4/b27f2fc6d9fca459d2d6a21c74c6fa04.jpg)
Answered by
9
→ Hey Mate,
→ Given Question:-
→
→ Solution:-
⇒ (2y + 3)(6y + 7) = (4y +5)(3y + 2)
⇒ 12y²+14y+18y+21 = 12y + 8y+15y+10
⇒ 12y² + 32y + 21 = 12y² + 23y + 10
⇒ 32y + 21 = 23y + 10
⇒ 32y - 23y = 10 - 21
⇒ 9y = -11
⇒ y =
⇒ ∴ The Answer is → y =
--------------------------------------------------
Similar questions